IMPLICATION OF THE FIXED COMBINATIONS IN THE HYPERTENSION TREATMENT - Z. D. Kobalava; J. V. Kotovskaya (Рациональная фармакотерапия в кардиологии, 2016)
The role of fixed combinations in the hypertension (HT) treatment is discussed. Theoretical and practical aspects of combination therapy, principles of rational combination therapy are present. Current guidelines on the use of fixed dose combinations, including start antihypertensive therapy are analyzed. Classification of combinations, advantages and limitations of some of them implementation are also presented. Significance of beta-blocker bisoprolol and thiazide diuretic hydrochlorothiazide fixed combination (Lodoz) is shown in HT treatment.